Cytotoxic activity of phenolic compounds in Bairui Granules obtained from the Chinese medicinal plant Thesium chinense - Zhang, Shaobin; Chen, Hong; Hua, Juan; Luo, Shihong (Frontiers in Chemistry, 2024)
The Chinese medicinal plant Thesium chinense Turcz. is the only plant used in the manufacture of Bairui Granules. However, to date, there has been very little research into the cytotoxic activity of active substances derived from Bairui Granules. Using chemical separation and spectroscopic methods, phenolic compounds 1-5 were identified as methyl-p-hydroxycinnamate, vanillin, kaempferol, isorhamnetin-3-Oglucoside, and astragalin, respectively. UPLC-MS/MS analyses revealed that compounds 1-5 were present at concentrations of 0.006 ± 0.002, 1. 63 ± 0.87, 3.65 ± 0.83, 26.97 ± 11.41, and 27.67 ± 2.91 μg/g, respectively in Bairui Granules.Compounds 1, 2, and 4 were detected here for the first time in Bairui Granules. Using co-culture experiments, isorhamnetin-3-O-glucoside (4) was found to be beneficial to the proliferation Chinese hamster ovary (CHO) cells (6.46 ± 0.86% to 38.45 ± 9.04%), natural killer cells from human umbilical cord blood (UCB NK cells) (25.68 ± 0.02% to 70.81 ± 0.26%), and mesenchymal stem cells from human umbilical cord blood (UCB MSC cells) (1.66 ± 0.05% to 27.64 ± 0.51%) when the concentration was similar to that found in Bairui granules. Moreover, vanillin (2) was conducive to UCB 2 NK cells proliferation (28.21 ± 0.44%) at a concentration of 64 μg/mL, while maintaining cell viability. UCB NK cell proliferation was promoted at rates of 41.03 ± 0.48% to 67.22 ± 0.68% when astragalin (5) was present at low concentrations (8 and 16 μg/mL). Methyl-p-hydroxycinnamate (1) and vanillin (2) at different concentrations both had an inhibitory effect on the proliferation of natural killer cells from human peripheral blood (PB NK cells), but the inhibitory concentration ranges of these compounds were not equivalent to the concentration ranges of the compounds in Bairui Granules. These results provide a foundation for the safe use of Thesium chinense preparations.